DEVELOPMENT OF ONLINE SNAKE AND LADDER MEDIA THROUGH GENIALLY TO IMPROVE THE LEARNING OUTCOMES OF IPAS STUDENTS OF GRADE V SDN HARGORETNO 2 KEREK DISTRICT - Gita Lestari, Khuddrotin Sri Suluh; Agustin, Ina (Pedagogic Research-Applied Literacy Journal, 2025)
This research aims to develop online snake and ladder media through Genially to improve the learning outcomes of social studies of grade V students of SDN Hargoretno 2 Kerek District who meet valid, practical, and effective criteria. This type of research is Research and Development (R&D) with the ADDIE model. The test subjects included material experts, media experts, linguists, teachers, and 24 students of class V. Research instruments included validation sheets, observations, interviews, response questionnaires, and student tests. The validation results showed 94% subject matter experts, 88% media experts, and 84% linguists (all of which are very valid). The teacher's response questionnaire obtained 80% and the student 86% (practical), while the student's test results showed classical completeness of 88% (very effective). Thus, the online snake and ladder media through Genially is declared valid, practical, and effective to be used in social studies learning to improve student learning outcomes.